Brake load characterization of heavy-duty vehicles - Achmad Munthahar, Sayid; Dhamane, Bhumika; Randby, David; Suresh, Nandu; Wurzinger, Jakob (My University, 2024)
In the fast-changing automotive world, more vehicles have zero tail-pipe emissions due to electrification. Global and local air quality has increased in recent times due to the implementation of legislation regarding tail-pipe emissions. Regulators are now looking at other sources of emissions, like particulate matter from brakes and tires, which have severe health effects. The particulate matter can enter the airways and if it is small enough, it can travel down to the lungs and even further into the bloodstream. The particle sizes can be divided into PM10, PM2.5, and Ultra-fine particles. Legislation for PM10 will be implemented regarding brake wear in the new Euro 7 legislation for light-duty vehicles in 2025 and something similar to this is expected for heavy-duty vehicles. The stakeholder for this project is Volvo Group, which has been involved during the whole project. This project mainly focuses on the emissions caused by disc brakes on Volvo’s Internal Combustion Engine (ICE) and Battery Electric Vehicle (BEV) heavy-duty vehicles. Field-test datasets from several ICE and BEV trucks, along with Volvo’s brake test rig data are used to estimate brake wear based on brake temperature and braking energy. Data analysis was performed on the dataset and brake wear estimation was done to characterize the braking behaviors of ICE and BEV trucks and determine which affects the brake wear the most. An in-depth analysis was performed by doing a multivariate analysis. The in-depth analysis resulted in the identification of four different clusters that were characterized by their unique driving behavior. From this exploration, it becomes evident that several factors influence brake wear, with temperature emerging as a prominent indicator linked to driving behavior.